Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Express as a single logarithm with a coefficient of 1:

$$ 2(\ln(x)-\ln(x+1))-3(\ln(x^2)-\ln(x^2-1)) $$ I've been trying for nearly an hour and can't seem to find the answer, can anyone help plz :S

share|improve this question

2 Answers 2

up vote 3 down vote accepted

Looks like this what you are looking for: [first note that $\ln a+\ln b=\ln(ab)$, $\ln a-\ln b=\ln(a/b)$ and $x\ln a=\ln (a^x)$; assuming all the $\ln$'s exist]

Your expression $$=2\ln x+3\ln(x^2-1)-[2\ln(x+1)+3\ln(x^2)]$$ $$=\ln[x^2.(x^2-1)^3]-\ln[(x+1)^2.(x^2)^3]$$ $$=\ln\frac{x^2.(x^2-1)^3}{(x+1)^2.x^6}$$ $$=\ln (1+\frac{1}{x})(1-\frac{1}{x})^3$$

share|improve this answer

Use the following rules for logarithms:

$$\ln(a)-\ln(b) = \ln\left(\frac{a}{b}\right)\\ c\cdot \ln(d) = \ln(d^c)$$

share|improve this answer
    
Did you mean $c\ln(d)=\ln(d^c)$? –  E.O. Sep 19 '12 at 4:22
    
@E.O. Whoops. Yes. I've edited to fix the error. –  Richard Sullivan Sep 19 '12 at 12:03

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.